Unraveling determinants of integrated farming systems adoption for sustainable livelihood and dietary diversity - Raghavendra, K. J.; John, Jacob; Jacob, D.; Rajendran, T.; Prusty, A. K.; Ansari, Meraj Alam; Ravisankar, Natesan; Kumar, Sunil; Singh, Raghuveer; Shamim, Mohammad; Punia, Peyush; Nirmal; et al. (Frontiers in Nutrition, 2024)
Introduction: Over the years, smallholders are facing more vulnerability to risk and uncertainties in India due to their dependence on cereal crops. One way to reduce this risk can be achieved through diversified agriculture and integrating different practices for efficient resource utilization adopting farming systems approach. Integrated farming system (IFS) is one such technique that provides yearround income from different components of enterprises. However, decision to adopt IFS may be determined by several characteristics of farmers which needs to be delineated through impact analysis to harness the benefits of systems approach.Methods: This study analyses the economic effects of integrated farming systems and assesses its determinants, as well as the dietary diversity pattern of farmers in two states of southern India i.e. Kerala and Tamil Nadu. A multistage sampling technique was used to obtain cross-sectional data from 367 farmers randomly chosen from one district from Kerala and two district from Tamil Nadu. The participants have Crop + Horticulture + Animal husbandry (45.45%) as major system, whereas, nonparticipants have Crop + Animal husbandry (44.35%) as predominant system. Coarsened exact matching and logit regression methods were used to evaluate the economic impacts of IFS and its influencing factors.The findings of the study indicate that age, education, livestock holding, access to credit, and plantation area have a positive and significant effect on participation by farmers in the programme. The matching results show that adoption of IFS resulted into significant economic impact, generating an additional gross income of Rs. 36,165 ha -1 and a net income of Rs. 35,852 ha -1 , and improving the dietary diversity of farm households by 8.6% as compared to non-adopters.Discussion: This study suggests that IFS is a promising approach for improving farmers livelihood, economic gains and nutritional security. Therefore, the integrated farming systems models need to be upscaled through convergence of government schemes in other regions of India to support smallholders' farming.